Implementasi Model Pembelajaran Contextual Teaching and Learning Berbantuan Media Mind Mapping untuk Meningkatkan Pemahaman Konsep Matematika - Putri, Prihastini Oktasari; Febriana, Rina; Malini, Hema (Wacana Akademika: Majalah Ilmiah Kependidikan, 2024)
This study aims to investigate the improvement of students' understanding of mathematical concepts in class VII C of SMP Muhammadiyah 8 Yogyakarta by implementing the Contextual Teaching and Learning (CTL) model with the assistance of mind mapping media. The method applied is Classroom Action Research consisting of two cycles, each cycle involving four stages: planning, implementation, observation, and reflection. The research subjects are 28 students from class VII C of SMP Muhammadiyah 8 Yogyakarta. The results of the study indicate that the application of CTL with mind mapping is effective in enhancing students' understanding of mathematical concepts. This is evidenced by the average scores increasing from 51.80 in the pre-cycle, to 59.50 in Cycle I, and reaching 85.80 in Cycle II. Improvement is also observed in the percentage of understanding mathematical concepts in each indicator, rising from 50.19% in the pre-cycle to 82.88% at the end of Cycle II. This demonstrates the effectiveness of the CTL model with mind mapping in enhancing students' mathematical comprehension.